A flexible resistive switching device for logical operation applications in wearable systems. (December 2022) - Zhu, S.; Sun, B.; Zhou, G.; Ke, C.; Guo, T.; Zhao, H.; Yang, F.; Zhang, Y.; Wu, Y.A.; Zhao, Y.
Abstract: As an emerging micro/nano device, memristor integrates functions, such as memory, sensing, and computing, and has similar internal dynamics to synapses, showing great potential in neuromorphic computing and logical operations. In this work, a flexible memristor with Al/TiOx /Al/polyethylene terephthalate structure was developed to investigate the synergistic effect from the oxygen vacancy, H2 O molecule, and NaCl. A forming-free resistive switching (RS) behavior observed in the flexible memristor can be ascribed to the migration and accumulation of the oxygen vacancy and Schottky emission of the interfaces. This forming-free RS is sensitive to the NaCl and H2 O molecule because the Na + migration disturbs the oxygen vacancy filament and interplay between oxygen vacancy and H2 O molecules. The variation conductance modulated by the concentration of NaCl and H2 O molecules can represent the weight update incrementally that the online learning required. Therefore, the memristor has the potential to be used as a biosensor in human tissues or to realize the brain-like chip, which points out the research direction for the extension function of the memristor in wearable systems. Graphical abstract: Image 1 Highlights: A flexible memristor was developed to investigate the synergistic effect. The forming-free RS behavior is attributed to the oxygen vacancy and Schottky emission. This device is sensitive duo to the Na + migration disturbs the oxygen vacancy filaments. The variation conductance can represent the weight update for the online learning. The memristor has the potential to be used as a biosensor in human tissues.